Etre migrant et vivre en squat - Céline Bergeon; Anne-Cécile Hoyez (L'Espace Politique)
This article intends to consider the « squats of migrants » as an opportunity to study the social and political processes that occur at the intersection between health, healthcare and residential trajectories. The demonstration is based on a series of observations led in a micro-space that is stigmatised in public policies (the squat), in groups also stigmatised (migrants), privileging an approach politically orientated and also centred on intimacy (health). This article reveals that health issues cannot be disconnected from the complexity of social relations occurring in the squats, and from political dynamics at local scale. Indeed, we can observe a set of conflicting situations and/or solidarity that can be alternatively obstacles to healthcare access, or, at the contrary, a tool to favour medical and medico-social care. Results arise from fieldwork researches led in 2013 and 2014 in Rennes and Poitiers (France). The first section of the article comes back on the theoretical basis regarding health, migration and precarious housing. The second one highlights the contexts and rhythms of residential experiences in squats for migrants. The third section proposes a renewed analysis of the complex, political and social dynamics that take place at the micro-scale of a squat, via the issues of health and healthcare access.